Skeletal Microstructures of the Chiton Ischnochiton hakodadensis and a Comparison with the Cambrian Halkieria - Zhang Xiaochuan; Yao Jinxian (Acta Geologica Sinica - English Edition, 2014)
Halkieria is an Early Cambrian fossil genus with proposed phylogenetic affinities ranging from stem group lophotrochozoan to stem-group aculiferan. Skeletal similarities are often cited as evidence in support of a mollusk interpretation for Halkieria and related Cambrian fossils. The skeletal microstructures of the polyplacophoran mollusk (chiton) Ischnochiton hakodadensis, which bears perinotum elements resembling sclerites of halkieriids and other coeloscleritophoran small shelly fossils (SSFs), were studied to evaluate the interpretations. There are both similarities and differences between chiton skeletal structures and halkieriid sclerites: 1) the head valve of I. hakodadensis and the dorsal shell of Halkieria evangelista share a similar pattern of fine concentric growth lines, but halkieriid dorsal shells lack other polyplacophoran valve characteristics, including V-shaped indentation, radiate ribs; 2) the arrangement of I. hakodadensis perinotum elements in three zones is somewhat similar to the arrangement pattern of halkieriid sclerites; 3) the inner perinotum scales of I. hakodadensis (approximate to 200 m in diameter) have a base and a blade, remarkably similar in morphology to halkieriid palmate sclerites (approximate to 400 m in diameter). However, I. hakodadensis perinotum scales are nearly solid whereas halkieriid sclerites are hollow. These observations add a microstructural dimension to the skeletal comparison between mollusks and halkeriids, and may prove to be useful in resolving the phylogenetic affinity of Halkieria and the Halwaxiidae. Geosciences, Multidisciplinary SCI(E) 0 5 1378-1387 88